2017
DOI: 10.1097/cco.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy: a new treatment paradigm in bladder cancer

Abstract: Purpose of reviewT-cell checkpoint blockade has become a dynamic immunotherapy for bladder cancer. In 2016, atezolizumab, an immune checkpoint inhibitor, became the first new drug approved in metastatic urothelial carcinoma (mUC) in over 30 years. In 2017, nivolumab was also approved for the same indication. This overview of checkpoint inhibitors in clinical trials focuses on novel immunotherapy combinations, predictive biomarkers including mutational load and neoantigen identification, and an evaluation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…45 The possibility of combination therapy upregulating mechanisms of resistance pathways will need to be further explored in our model. Recent US Food and Drug Administration approval of atezolizumab (anti-PD-L1mAb) and nivolumab (anti-PD -1mAb) for treatment of metastatic urothelial carcinoma 46 has brought into question the role of immune therapy earlier in the treatment of UC. Our analysis of patients who have undergone Ad-IFNα/Syn3 (Instiladrin) therapy showed upregulation of cytokines key for immune infiltration, T cell markers, and PD-L1 (and CTLA-4) immune evasion markers, suggesting that these patients may be prime candidates for PD-1 blockade in addition to their gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…45 The possibility of combination therapy upregulating mechanisms of resistance pathways will need to be further explored in our model. Recent US Food and Drug Administration approval of atezolizumab (anti-PD-L1mAb) and nivolumab (anti-PD -1mAb) for treatment of metastatic urothelial carcinoma 46 has brought into question the role of immune therapy earlier in the treatment of UC. Our analysis of patients who have undergone Ad-IFNα/Syn3 (Instiladrin) therapy showed upregulation of cytokines key for immune infiltration, T cell markers, and PD-L1 (and CTLA-4) immune evasion markers, suggesting that these patients may be prime candidates for PD-1 blockade in addition to their gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Other immune-checkpoint players such as cytotoxic T lymphocyte-associated antigen (CTLA-4), which is expressed in T lymphocytes surface and binds B7 on antigen-presenting cells (APCs)-thus impeding the co-stimulatory signal necessary for T-cell activation-also constitutes a target for immune-checkpoint inhibitors, like Ipilimumab. In fact, combinations of both types of inhibitors (anti-PD-1/PD-L1 combined with anti-CTLA-4 agents) are currently undergoing clinical trials for BlCa patients [31,32], following the success observed in melanoma patients [33].…”
Section: Immune Therapies-brief Overview In Bladder Cancermentioning
confidence: 99%
“…Treatment-related side effects of fatigue, and the impact on daily activities, are also reported as relevant to these patients [5], as well as issues with self-esteem, embarrassment, and difficulty engaging in sexual relationships [4, 7, 8]. Emerging novel treatments [9] have accelerated interest in developing and validating patient-reported outcome (PRO) collection instruments to gain a full understanding of UC and disease impact, information important for patients and clinicians. In addition, PRO data can inform the benefit/risk assessment for regulators and payers [10].…”
Section: Introductionmentioning
confidence: 99%